Impact on fetal outcome following burns in pregnancy - Mehta, Harsh Rajeev; Wasadikar, Pravinkumar P. (International Surgery Journal, 2021)
Background: The incidence of female burn patients of reproductive age varies from 0.6%-15% in different series with highest incidence reported from India.Foetus is at high risk due to burns injury, which is often associated with a high rate of fetal mortality. Methods: All cases of burns injury encountered during pregnancy admitted at our tertiary care hospital were included in this study over a span of two years from 2017 to 2019. A total of 20 cases were included in the study. Patients with burns injury from 5 to 100% body surface area were included in this study. Results: Fetal deaths occurred in 11 out of the total 20 cases amounting to 55% overall fetal mortality. Conclusions: Burns during pregnancy requires adequate resuscitation especially in initial stages. There is 100% fetal death outcome for burns greater than 50% body surface area.